Pengaruh Word of Mouth, Influencer dan Personal Selling Terhadap Keputusan Pembelian Konsumen Pisang Keju Bengkulu - Ayu Ningsih, Nofri Tri; Puspita, Venny; Safrianti, Sintia (ARBITRASE: Journal of Economics and Accounting, 2023)
Business people are required to be able to attract consumer purchasing decisions so that their business can develop so that they can achieve success. In attracting consumer purchase decision attitudes, business people must pay attention to word of mouth, influencers and personal selling. The purpose of this study was to determine the effect of word of mouth, influencers and personal selling on consumers' purchasing decisions of Bengkulu Cheese Bananas. This study uses a quantitative method with an explanatory approach. The population in this study were all consumers who shop at Banana Cheese Bengkulu with a total sample of 190 respondents. The sampling technique in this study is accidental sampling technique. Then for the analytical method used is multiple regression analysis. To test the hypothesis, researchers used the T test and F test with the help of SPSS. Based on the results of research and analysis, it shows that word of mouth, influencer and personal selling variables have a positive and significant effect on consumer purchasing decisions at Banana Cheese Bengkulu. The results of multiple linear regression, from variable X1 (word of mouth), variable X2 (influencers), variable X3 (personal selling) are considered to be able to increase consumer purchasing decisions. The results of this study can be concluded that word of mouth, influencer and personal selling variables have a positive and significant effect on consumer purchasing decisions at Banana Cheese Bengkulu